PENGGUNAAN APLIKASI LE-DIABET DALAM PENGELOLAAN DIABETES MELITUS: STUDI KESIAPAN DENGAN TECHNOLOGY ACCEPTANCE MODEL - Lina Erlina; Dhea Sena Kurnia Putri; Nandang A Waluya; Ali Hamzah (Poltekkes Kemenkes Bandung, 2025)
Le-Diabet is an innovative Android-based application designed by researchers to support comprehensive management of diabetes mellitus (DM) through five main pillars: education, diet, physical activity, self-monitoring of glucose, and diabetes therapy. The study aimed to evaluate the readiness of the Le-Diabet application in managing blood glucose levels in DM patients. The study involved 82 respondents with DM who used the Le-Diabet application selected using the purposive sampling method. Data were collected using the Technology Acceptance Models (TAM) questionnaire and analyzed using five main indicators of technology readiness, namely perceived ease of use, perceived usefulness, intention to use, attitude toward behavior, and actual use. The results of the study showed that the Le-Diabet application is ready to be used by the community with the majority of respondents having good and very good perceptions of ease (72%), usefulness (99%), and interest in use (89%). Although there were 12% of respondents who felt uncomfortable with the ease of use, factors such as health education and family support contributed positively to the positive attitudes of respondents in accepting this application (99%). The actual level of use was recorded in the good and very good categories (95%), indicating great potential in helping independent diabetes management. The study concluded that Le-Diabet has good readiness and can be implemented more widely, but further development is needed to maximize respondent comfort in using the Le-Diabet application.